Pengaruh Kesadaran Wajib Pajak, Sanksi Pajak, dan Insentif Pajak Terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan Perkotaan dan Perdesaan (PBB-P2) di Kota Surabaya - Narisyah Evita Zharah; Sri Trisnaningsih (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the effect of taxation knowledge, tax penalties, and tax incentives on the compliance of land and building taxpayers in Surabaya City. This type of research uses a quantitative approach. The population used is all PBB-P2 taxpayers in Surabaya City totaling 820,366 taxpayers registered at the Surabaya City Regional Revenue Agency with the required sample of 170 taxpayers determined using probability sampling with simple random sampling method and the sample size using Hair's formula. The data collection technique used is a questionnaire that has been filled out by respondents, namely PBB-P2 taxpayers in Surabaya City. The questionnaire will use an online form in the form of Google Form through social media so that it is more flexible for respondents to answer the questionnaire. The analysis method in this study uses SmartPLS. The results showed that tax sanctions and tax incentives have an effect on compliance of land and building taxpayers, while taxpayer awareness has no effect on compliance of land and building taxpayers.